Combining computer aided food engineering and electro-heating applications as contribution to food processing sustainability - Marra, Francesco (Frontiers in Sustainability, 2023)
United Nations Sustainable Development Goal 7 (SDG7) is aimed to ensure the access to affordable, reliable, and sustainable and modern energy for all. According to World Bank, ensuring access to modern food cooking solutions is a key component to achieving for SDG7, and -since cooking is mainly based on heating processing- also the access to modern food heating solutions must be considered as a key component to achieving for SDG7. Electro-heating applications in food processing include all processes using the interaction of a food material or product with an electromagnetic field, as in microwave, radio-frequency, and moderate electric fields processing. These technologies involve the use of electrical and -more recently- electronic circuits and require professional figures in their design. As result, the installation cost of these technologies is way higher than installation cost for heating processes using fossil sources, as fuel for fire boilers, as an example. Furthermore, at industrial level, these technologies may require ad-hoc design. Consequently, the food processing industry is quite slow in embracing such technologies along the productive lines. Computer aided food engineering has been recognized as valuable approach to shifts the paradigm from trial-and-error-based design to model-based design, using digital tools for the virtual representation of a food product or process, predicting the behavior of it. This paper presents a viewpoint on the challenges and opportunity to combine computer aided food engineering and electro-heating applications as contribution to food processing sustainability